Negotiating Dissidence The Pioneering Women of Arab Documentary - Van de Peer, Stefanie (Edinburgh University Press, 2017)
Traces the very beginnings of Arab women making documentaries in the Middle East and North Africa (MENA), from the 1970s and 1980s in Egypt and Lebanon, to the 1990s and 2000s in Morocco and Syria.